Dead Sea Scrolls dan Reliabilitas Alkitab Dalam Perspektif Injili - Suyadi Tjhin (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
This article discusses Dead Sea Scrolls and the reliability of the Bible from an evangelical perspective. This review from an evangelical point of view is needed to give perspective to Christian academics, so that they can take a position related to the above mentioned topic. From the results of a study of the Dead Sea Scroll's contribution in relation to the reliability of the Bible, Dead Sea Scroll is indeed a historical and important finding in the field of archeology, especially in connection with the Bible, but it must be realized that not because of archeological evidence that makes the Bible trusted, the Bible can be trusted so there is evidence.